A new leaky wave antenna using wire‐loaded metagratings: The theoretical analysis and implementation. (2nd April 2022) - Al Soad, Odai Hassan Raheem; Sun, Haifeng; Fu, Jiahui; Wu, Qun
Summary: A new leaky wave antenna (LWA) based on wire‐loaded metagratings (MGs) is proposed, with the capability of successfully employing MGs for leaky modes. Periodic capacitive‐wired and inductive‐wired MGs are located on a dielectric substrate in the LWA framework and backed by a perfect electric conductor (PEC) layer. These MGs are partial radial surfaces to radiate energy using equivalent surface impedance with a local value of the complex wavenumber. A theoretical analysis has created a model for the equivalent electromagnetic fields produced via loaded‐wire MGs and generated the Z ‐matrix and S ‐matrix for a two‐port structure from the electromagnetic fields. As a result, a beam‐scanning range of 53° for the operating bandwidth of 9.9–11.9 GHz is achieved with a scanning sensitivity of 26.5°/GHz. Meanwhile, the realized gain is obtained up to 12.9 dB. The measurement and simulation results indicated that the MGs LWA was consistent. The proposed antenna performed admirably in beam‐steering communication systems. Abstract : The capability of MGs employed successfully for leaky‐wave antenna. MGs functioned as capacitive‐wired and inductive‐wired connected elements. MGs based on LWA framework can be used to control and form the farfield beam.